Conspiracies in the Egyptian palace : Unis to Pepy I - Kanawati, Naguib (Routledge, 2003)
This original study examines the claims for sensational intrigues in the 6th century Egyptian palace, culminating in the possible assassination of King Teti by his own bodyguards.